Effect of Parboiling on Thiamin, Protein and Fat of Rice - Padua, Adoracion B.; Juliano, Bienvenido O. (Wiley, 1974)
Parboiling decreased the thiamin content of rice. Nevertheless, milled parboiled rice contained more thiamin than milled raw rice at the same degree of milling because parboiling caused thiamin to diffuse inwardly. Both the degree of loss and the degree of diffusion depended on the severity of the heat treatment. Bran‐polish of parboiled rice had a higher fat and protein content than bran‐polish of raw rice at the same degree of milling because the starchy endosperm of parboiled rice had a greater resistance to milling and so the bran and the germ were more effectively removed. Milled parboiled rice tended to have lower protein content than milled raw rice. Starch content was lower in bran‐polish from parboiled rice.